KETAHANAN BUAH BEBERAPA KLON KAKAO (THEOBROMA CACAO L.) TERHADAP INFEKSI PENYAKIT BUSUK BUAH BERDASARKAN UJI DETACHED POD - Aisyah, Nurul; Rahmansyah, Rahmansyah; Muslimin, Muslimin; Suwastika, I Nengah (Univ. Tadulako, 2014)
One target on Cacao breeding program is to develop superior clone which resistance against major pest and diseases. In present time, Pod Rot disease is one of serious problem on the Cacao plantation system, including over the area of Central Sulawesi. The aim of this study was to identifiy the resistancy on five different clones of cacao (ICCRI 1, ICCRI 3, ICCRI 4, Local Sidondo and Green Local Sausu) from local farming in Central Sulawesi against Phytophthora pot rot infection based on detached pod assay. Sample were collected from the farming area of Sigi Biromaru, Palolo, and Sausu, over the harvesting period of February - May 2014. Mature and healthy pods were detached from the plant, then artificially inoculated by using Phytophthora-infected pericarp. Pod rot symptom and spreading area of fungi were observed dialy, then total area of infection on day-6 was used as disease rating scale. The outcome data showed that all pod of the clones were classified as a highly susceptible clones against pod rot disease. However, pod resistance level of each clones were statisfically different. Green Local Sausu and Local Sidondo were more resistant than other clones. This result suggesting that Local clones have been developing resistancy mechanism against Pod Rot disease.